1988
DOI: 10.1103/physrevlett.60.1073
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetism and superconductivity in oxygen-deficientYBa2Cu3

Abstract: Positive-muon spin-rotation and -relaxation measurements of the oxygen-deficient perovskite YBa2-Cu30 x have revealed local antiferromagnetic order for 6.0^x^6.4 with a Neel temperature TN that decreases rapidly with increasing oxygen content x. For slowly annealed samples with 6.35^x^6.5 the superconducting transition temperature T c increases smoothly with x from 25 K at x =6.348 to 60 K at x =6.507. Two such samples with x =6.348 and x =6.400 appear to "switch" from superconductivity to antiferromagnetic or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 232 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…For type-II superconductors in the vortex state in an applied field of B app ≪ B c2 (B c2 is the upper critical field) the square root of the second moment of the muon depolarization rate σ is inversely proportional to the square of the magnetic penetration depth: σ ∝ 1/λ 2 (Refs. 4,46,47) and therefore directly related to the superfluid density: ρ s ∝ 1/λ 2 ∝ σ. For a polycrystalline sample of a highly anisotropic and uniaxial superconductor the dominant contribution to the muon depolarization originates from the in-plane magnetic penetration depth λ ab = λ eff /1.31, where λ eff is an effective (averaged) magnetic penetration depth.…”
Section: Results and Analysis Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…For type-II superconductors in the vortex state in an applied field of B app ≪ B c2 (B c2 is the upper critical field) the square root of the second moment of the muon depolarization rate σ is inversely proportional to the square of the magnetic penetration depth: σ ∝ 1/λ 2 (Refs. 4,46,47) and therefore directly related to the superfluid density: ρ s ∝ 1/λ 2 ∝ σ. For a polycrystalline sample of a highly anisotropic and uniaxial superconductor the dominant contribution to the muon depolarization originates from the in-plane magnetic penetration depth λ ab = λ eff /1.31, where λ eff is an effective (averaged) magnetic penetration depth.…”
Section: Results and Analysis Detailsmentioning
confidence: 99%
“…Detailed muon spin rotation (µSR) studies of the magnetic penetration depth λ and the superfluid density ρ s ∝ 1/λ 2 were performed on poly-and single crystals of YBa 2 Cu 3 O x at ambient pressure. [3][4][5][6][7][8][9][10] However, the key question concerning the pairing mechanism responsible for high temperature superconductivity is still not resolved, and is subject of intense debates. Although it is widely believed that magnetic fluctuations play a dominant role in the pairing mechanism, 11 oxygen isotope effect (OIE) studies indicate that lattice degrees of freedom are essential for the occurence of superdonductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, SR studies on La 2 CuO 4 , 28 (La,Li) 2 CuO 4 , 29 La 2Ϫx Sr x CuO 4 , [30][31][32][33][34] and YBa 2 Cu 3 O y , 34,35 were performed to characterize magnetic phase diagrams as a function of hole concentration and also to study details of the spin glass states near xϭ0.05.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in the mixed ternary system (Sml-,Er,) Rh4B4 LT,SC and A F coexist for small Er concentrations, and t,he manner in which AB changes to ferromagnetism was considered [5]. In ra.re earth HT,SC it has been shown that in the mixed ternary system (La,-,Sr,) CuO,, the NQel temperature T, is still non-vanishing for replacements of La, by La,.o,Sro,2 [2]. Neutron-diffraction measurements on an oriented powder of YBa,Cu,Od have confirmed the presence of AF in this material [6].…”
Section: Introductionmentioning
confidence: 99%